Ferry Irwandi’s Communication Strategies in Deconstructing Mystical Beliefs on Youtube: A Social Construction of Reality Analysis - Muhammad Efendi; Iman Sumarlan (Lembaga Aneuk Muda Peduli Umat, Bekerjasama dengan LaKaspia, 2026)
This study aims to examine Ferry Irwandi’s communication strategies in constructing counter-narratives to mystical beliefs on Indonesian YouTube using Berger and Luckmann’s Social Construction of Reality framework. The proliferation of mystical content on YouTube has contributed to the normalization of supernatural beliefs within digital culture, particularly narratives surrounding witchcraft, indigo phenomena, and shamanistic practices. Employing a qualitative case study design, this research analyzes three YouTube videos through video observation, transcription, narrative and rhetorical analysis, and examination of audience comments. The findings indicate that Irwandi constructs externalization through critical narratives that expose logical inconsistencies in mystical claims, objectivation through empirical references and visual simplification, and internalization through audience responses marked by acceptance and resistance. Reflective content reinforces communicator credibility through clarification of positional stance, while collaborative dialogic formats strengthen rhetorical structure and expand social legitimacy for rational critique. This study demonstrates that the deconstruction of mysticism in digital media operates as a contested process of social meaning construction shaped by narrative strategy, rhetorical authority, visual representation, and audience interpretation.